Conservação de Lippia sidoides do norte de Minas Gerais e Vale do Jequitinhonha: localização, coleta, ecogeografia, crescimento, modo de reprodução e divergência genética - Marco Tulio Pinheiro de Melo (2012)
The "alecrim-pimenta" (Lippia sidoides) is a medicinal plant with important antiseptic and antimicrobial activity. The plant is considered as prioritary to conservation and management. Another important point is the implantation of an in vivo germplasm bank, which enables the development of studies of growth, reproduction mode and genetic diversity with several accessions of the specie and, consequently, generates essential information to define conservation strategies and genetic improvement. Therefore, the objective of this study was to characterize the sites of occurrence of the populations of alecrim-pimenta, evaluate the agronomic behavior and the genetic divergence of species accessions, and also determine the reproduction mode of the specie. Eighteen populations were sampled in the north of Minas Gerais regions and Jequitinhonha Valley between February 2010 and January 2011. On each expedition were recorded the geographic coordinates and collectedsamples of soil, leaves and cuttings to propagation. The agronomic experiment was carried out in the Instituto of Ciências Agrárias of Universidade Federal of Minas Gerais (ICA/UFMG), Montes Claros, Minas Gerais State. The accessions were evaluated on the experimental design of randomized blocks design, with 14 L. sidoides accessions with three replications. As two accessions had died, only twelve were analyzed through isoenzymes electrophoresis in starch gel, aiming to analyze its genetic divergence. The accessions were clustered following Tochers method. To the reproduction mode analysis, 30 flowers were collected from stock plants in medicinal vegetable garden of ICA/UFMG were used. According to the ecogeographic study, the accessions are between the coordinates 15°38'31.00" e 18°24'31.70" of South latitude and 42°15'47.90" and 44°16'5.30" West longitude, with an average altitude of 820m, ranging from 564 and 1264m. The essential oil content of the accessions in natural environment presented an averageof 3.40%, ranging between 0.28 and 7.78%. Approximately 78% and 67% of the populations occurred in dystrophic soil with high to medium acidity, respectively. The sites of occurrence of all populations presented very low levels of phosphorus. In relation to organic matter, the levels ranged between medium and good. The sampled regions presented sandy and medium soils. As for the biome, 78% of the populations occur in the Cerrado regions, 11% in areas of transition between Cerrado and Atlantic Forest and 11% in Atlantic Forest. Approximately 94% of the populations are in the tropical warm and under warm tropical, ranging from semiarid and semihumid. In relation to the precipitation, the sampled regions have annual average values less than 1000mm (17%), 1000 1200mm (50%), 1200 1500mm (22%) and higher than 1500mm (11% of the regions). The agronomic evaluation showed that the accessions presented significant differences to the variables: plant height, amount of leaves, stalk diameter, fresh and dry phytomass and essential oil production. In relation to the species reproduction mode, the pollen/ovule ratio of L. Sidoides was 1553 ± 443 pollen grains per ovule.The results of the genetic divergence showed the accessions ICA-05 and ICA-08 were the most dissimilar, while ICA-08 and ICA-12 presented the highest similarity by the isoenzymatic data. The genetic divergence by the agronomic data presented ICA-02 and ICA-09 as the most similar accessions and ICA-10 and ICA-12 as the lowest. Based on the results, it can conclude that the most of the sampled populations of L. sidoides occur naturally in poor and acid soils, in typical vegetation of Cerrado, with warm weathers, in areas with different precipitation levels and great variation in altitude. The accessions ICA-12, ICA-11, ICA-01, ICA-07, ICA-06 and ICA-04 show itself as the most promising to the yield of phytomass and essential oil, while ICA-10 was the less promising accession. The results of thymol content evidenced the significant potential of accession ICA-05. The pollen/ovule ratio indicates that the specie is facultative alogamous. It was observed high genetic variability in the studied accessions.